Komposisi dan Struktur Vegetasi pada Proses Suksesi di Hutan Rawa Gambut Sedahan Taman Nasional Gunung Palung, Kalimantan Barat - Istomo Istomo; Ari Fardian (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2021)
This study aims to analyze the species composition and vegetation structure in the succession process in the Sedahan Peat Swamp Forest, Gunung Palung National Park. Data collection using vegetation analysis on three forest types namely young secondary, old secondary, and climax forest. Research shows that the number of tree species found is decreasing in the forest the older ones, show the species that are able to survive the succession process. The highest important value index of the seedling level are ubah (Syzygium leptostemon) in the climax (87.1%), saplings are mahang (Macaranga pruinosa) in young secondary (84.9%), poles and trees are mahang in old secondary by also 135.5% and 137.1%. Community at pole growth rate in forest young secondary and young secondary have the largest significant Index of Similarity value have relatively the same conditions. Canopy stratification found in forests secondary forest is strata C and B while climax forest is C, B, and A. Keywords: peat swamp forest, species composition, succession process, vegetation structure